A granular fertilizer carrier impregnated with metsulfuron injures centipedegrass when applied at excessive rates. Issue 1 (30th March 2021) - Gonçalves, Clebson G.; McElroy, J. Scott; Brown, Austin M.; McCullough, Patrick E.; Leon, Ramon Gonzalez; McCarty, Lambert B.
Abstract: To understand the observed injury, the objectives of this research were (a) to correlate combination of nitrogen fertilization and metsulfuron [methyl 2‐(4‐methoxy‐6‐methyl‐1, 3, 5‐triazine‐ 2‐ylcarbamoylsulfamoyl) benzoate] with excessive injury to centipedegrass [ Eremochloa ophiuroides (Munro) Hack.] and (b) to determine how simultaneous high nitrogen fertilizer and the resulting increased metsulfuron rates exacerbated the observed injury. Field research was conducted at Auburn University, Clemson University, University of Florida, the University of Georgia, and H&H Sod Company in St. Cloud, FL, in 2015. Treatments included: a nontreated control, fertilizer alone (32–0–10 N–P–K and 32–0–9 N–P–K), metsulfuron (60% water‐dispersible granules), metsulfuron on an inert carrier, metsulfuron on fertilizer (32–0–9 N–P–K), and atrazine (2‐chloro‐4‐ethylamino‐6‐isopropylamino1, 3, 5‐triazine) on fertilizer (29–0–10 N–P–K) applied at rates ranging from one to eight times the labeled rate. Metsulfuron on fertilizer induced more injury as the rate increased than any other treatment across all locations. The highest rates of metsulfuron on fertilizer (348.5 lb N acre –1 plus 0.24 lb metsulfuron acre –1 ) reduced centipedegrass ground cover by 79 and 81% at 28 and 42 d after treatment, respectively. From these data, we conclude that metsulfuron applied on a granular fertilizer carrier can induce greater injury than metsulfuron on an inert granular carrier. Core Ideas: "Weed and feeds" are herbicides formulated with a granular fertilizer as the carrier. Centipedegrass injury may be caused by a fertilizer–metsulfuron interaction. Overapplications of metsulfuron on fertilizer may result in injury to centipedegrass lawns.